A Posteriori Error Estimates of Discontinuous Streamline Diffusion Methods for Transport Equations (Communications in Computational Physics, 2018)
Residual-based posteriori error estimates for discontinuous streamline diffusionmethods for transport equations are studied in this paper. Computable upperbounds of the errors are measured based on mesh-dependent energy norm and negativenorm. The estimates obtained are locally efficient, and thus suitable for adaptivemesh refinement applications. Numerical experiments are provided to illustrate underlyingfeatures of the estimators.
Keywords: A posteriori error estimates; discontinuous streamline diffusion methods; transport equations.